Torsion Testicular Patient Characteristics - Safendra Siregar; Devlin Alfiana; Jason Liarto; Zola Wijayanti (Faculty of Medicine, Universitas Padjadjaran, 2021)
Testicular torsion is an emergency urological condition that is caused by the torsion of the spermatic cord structures, causing disruption of circulation of the affected testicle. This study aimed to describe the characteristics of patients with testicular torsion treated at Dr. Hasan Sadikin General Hospital Bandung from January 2016 to January 2020. This was a retrospective descriptive study on 34 medical records of patients diagnosed and treated for testicular torsion. Nine patients (29.4%) were <20 years old and 25 patients were >21 years old. The onset was mostly between 6 to 24 hours (38.2%), followed by between 2–7 days (23.5%), less than 6 hours (20.6%), between 1–2 weeks (8.8%), and between 2–4 weeks (8.8%). Left testicular torsion were more frequent than the right torsion (61.8% vs. 38.2%). The etiology of the torsion was mostly idiopathic with no identifiable precedent (88%). Orchidectomy was more frequently performed compared to orchiopexy (78.4% vs. 21.6%). All but one patient (97.1%) presented with testicular pain as the main symptom. Patients presented mostly with a high risk TWIST score (64.7%); however, more presented with low risk compared to the intermediate risk TWIST score (26.5% vs. 8.8%). Orchidectomy is the most frequently performed operation on pre-pubertal and adult patients, possibly due to relatively delayed presentation (>24 hours) to the hospital to receive treatment. Patients were mostly younger; predominantly with high TWIST score and affected left testicle.